Understanding The Effect of Supply Chain Complexity in Determining Organisational Responses to Critical Supply Chain Failure – Case Study Analysis of The Rolls-Royce PLC Supply Chain - Davies, Andrew S (2011)
The study examines the relationship between complexity and organisational responses to critical supply chain failure, it also assess whether the operating principles of high reliability organisations ("HROs") can offer any benefit to commercial organisations in avoiding or mitigating the impact of future critical failure events.